Thermal analysis of the triple-phase asynchronous motor-reducer coupling system by thermal network method. (October 2020) - Chen, Mingzhang; Zhuang, Wuhao; Deng, Song; Zhu, Chengjie
As the core components of mechanical power system, triple-phase asynchronous motor and reducer are required strictly for temperature control. In this paper, the triple-phase asynchronous motor and the reducer are regarded as a coupling system, and thermal network method is used to predict the temperature field distribution of the coupling system. The predicted temperature of the thermal network method is consistent with the experimental result and the finite-element analysis. Furthermore, analysis shows that motor output power, coefficient of friction between teeth and lubricating oil parameters have a great effect on reducing the temperature of the coupling system.